This Is Not an Atlas : A Global Collection of Counter-Cartographies - kollektiv orangotango+ (2018)
Over the last years, kollektiv orangotango has gathered more than 40 counter-cartographies from all over the world. As the first of its kind, this collection shows how maps are created and transformed as part of political struggles, for critical research, or in art and education: from indigenous struggles in the Amazon to the anti-eviction movement in San Francisco, from defending commons in Mexico to mapping refugee camps with balloons in Lebanon, from slums in Nairobi to squats in Berlin, from supporting communities in the Philippines to accusing sexual harassment in Cairo. This Is Not an Atlas seeks to inspire, to document the underrepresented, and to be a useful companion for those seeking to become counter-cartographers themselves.